Challenges of Evidence-Based Practice and Nursing Education in Sub Saharan Africa: An Integrative Review - Kabir Ozigi Abdullahi, Shahrzad Ghiyasvandian, Marzieh Hasanpour, Nahid Dehghan Nayeri, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: This paper was conducted to explore the challenges of evidence-based practice and nursing education in sub-Saharan Africa. Methods: An integrative review study was conducted with a search of PubMed, Web of Science, Scopus and Science Direct, the record so collected were identified, screened and reviewed. Results: The search conducted produced a total of 1,296 records: 1,106 from PubMed; 90 from Web of Science; 54-Scopus and 46- Science direct. Seven themes emerged thus: Resources and infrastructure; Inadequate facilities and capacity building; Funding problem; Collaboration and teamwork; Curriculum reform; professional regulation; and nursing culture. Conclusions: It is evidently apparent that in order to ensure improved quality and quantity of production, and the adoption of EBP in the care, developmental partners and government have to increase the allocation of fund for infrastructural development, teaching and learning materials as well as hospital facilities to create an enabling environment for the smooth running of the evidenced practice in Nursing. Keywords: Evidence-based Practice; Challenges; Nursing education; African, Sub Saharan